Occupational Burden of Cancer in Korea - Eun-A Kim; Hye-Eun Lee; Seong-Kyu Kang (Elsevier, 2010)
Objectives: The extent of the occupational cancer burden has rarely been estimated in Korea. The aim of this study is to provide an estimation of the population attributable fraction (PAF) of occupational cancer in Korea. Methods: Nine kinds of Group 1 carcinogens addressed by the International Agency for Research on Cancer (IARC) and 7 kinds of cancer were selected for the target carcinogens and diseases, respectively. The prevalence of carcinogen-exposed workers was estimated and correction factors were applied so that the value would be representative of the total population. Data on relative risk (RR) were taken from IARC reports and were compared with the RRs from the studies on Korean workers. The PAF was estimated according to Levin's formula. Results: The proportion of the general Korean population exposed to carcinogens was 9.7%. The PAF of total cancer was 1.1% for incident cancer cases and 1.7% for cancer deaths. The PAFs of lung cancer and leukemia were 7.0% and 4.5%, respectively. With the RRs reported from Korean studies, the PAF for lung cancer and leukemia were 3.7% and 3.4%, respectively. Conclusion: The PAF in this study (1.1%) was lower than that reported in previous studies (2-4%) from developed countries. Considering that only 9 of the 29 kinds of Group 1 carcinogens were included in this study, the PAF might be underestimated. However, because the process of industrialization in Korea differs from that which occurred in other developed countries, 1.1% of the PAF might be appropriate for Korea.